2015
DOI: 10.1542/peds.2014-2968
|View full text |Cite
|
Sign up to set email alerts
|

Allergy in Children in Hand Versus Machine Dishwashing

Abstract: BACKGROUND AND OBJECTIVE: The hygiene hypothesis stipulates that microbial exposure during early life induces immunologic tolerance via immune stimulation, and hence reduces the risk of allergy development. Several common lifestyle factors and household practices, such as dishwashing methods, may increase microbial exposure. The aim of this study was to investigate if such lifestyle factors are associated with allergy prevalence.METHODS: Questionnaire-based study of 1029 children aged 7 to 8 years from Kiruna,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…In a Swedish study hand dishwashing, which is presumed to be less effective in eliminating microbes when compared with machine dishwashing, was associated with less eczema and less ''total allergy'' (ie, a combination of eczema, asthma, and/or allergic rhinoconjunctivitis). 7 The protective effect of hand dishwashing was stronger in children eating fermented foods, farm-bought foods, or both, raising the possibility of specific sources of food-borne microbes being transmitted through the presumably less hygienic method of hand dishwashing. The same research group reported on the parental behavior of infant pacifier ''cleaning'' by putting it in the parent's mouth before giving it back to the infant; 48% of the cohort reported this practice in the first 6 months of life.…”
Section: Clean (And Not So Clean) Livingmentioning
confidence: 99%
“…In a Swedish study hand dishwashing, which is presumed to be less effective in eliminating microbes when compared with machine dishwashing, was associated with less eczema and less ''total allergy'' (ie, a combination of eczema, asthma, and/or allergic rhinoconjunctivitis). 7 The protective effect of hand dishwashing was stronger in children eating fermented foods, farm-bought foods, or both, raising the possibility of specific sources of food-borne microbes being transmitted through the presumably less hygienic method of hand dishwashing. The same research group reported on the parental behavior of infant pacifier ''cleaning'' by putting it in the parent's mouth before giving it back to the infant; 48% of the cohort reported this practice in the first 6 months of life.…”
Section: Clean (And Not So Clean) Livingmentioning
confidence: 99%
“…According to the experiment of hesselmar et al [14], children with family history of allergy, those whose parents sucked their pacifiers to clean them had less likely to have asthma, eczema, or allergic sensitization, the other experiment given by Hesselmar et al [15] in comparison to the family using hand to wash dishes and using dishwasher, the family who washed dishes by hand had less chance of developing allergy in comparison to other. Immune system is regulated by gut microbiota, as the bacterial colonization takes place immune system is stimulated, at the early beginning they block the gut epithelial cell producing antibacterial substance, creating tight junction and stimulating IgA, second is to identification between the symbiotic and pathogenic bacteria by immune system at gut mucosal surface, the intestinal micribiota can regulate interleukin (IL)-1 and toll like receptors, even directly influence dendritic cell, Tcell, B lymphocytes and epithelial and stromal cell, dysbiosis causes chronic inflammation resulting in metabolic dysfunction and immune regulated disease by interfering immune regulatory system.…”
Section: Immunes Systemmentioning
confidence: 99%
“…For example, recent studies show that higher consumption of traditionally fermented foods is associated with reduced risk of atopy in adults [255], lower rates of allergy in children [256], anxiety in young adults [257], and eczema in offspring when consumed during pregnancy [258]. However, in North America, affluent Caucasian women maintaining healthy lifestyles—those at far lower risk of depression—are significantly more likely to consume fermented foods and encephalobiotics [259].…”
Section: Hygiene Hypothesis Dysbiotic Driftmentioning
confidence: 99%